Development of Nanomaterials to Target Articular Cartilage for Osteoarthritis Therapy - Rao, Chenyu; Shi, Sirong (Frontiers in Molecular Biosciences, 2022)
Osteoarthritis (OA) is an obstinate, degradative, and complicated disease that has drawn much attention worldwide. Characterized by its stubborn symptoms and various sequela, OA causes much financial burden on both patients and the health system. What’s more, conventional systematic therapy is not effective enough and causes multiple side effects. There’s much evidence that nanoparticles have unique properties such as high penetration, biostability, and large specific surface area. Thus, it is urgent to exploit novel medications for OA. Nanomaterials have been sufficiently studied, exploiting diverse nano-drug delivery systems (DDSs) and targeted nano therapeutical molecules. The nanomaterials are primarily intra-articular injected under the advantages of high topical concentration and low dosage. After administration, the DDS and targeted nano therapeutical molecules can specifically react with the components, including cartilage and synovium of a joint in OA, furthermore attenuate the chondrocyte apoptosis, matrix degradation, and macrophage recruitment. Thus, arthritis would be alleviated. The DDSs could load with conventional anti-inflammatory drugs, antibodies, RNA, and so on, targeting chondrocytes, synovium, or extracellular matrix (ECM) and releasing the molecules sequentially. The targeted nano therapeutical molecules could directly get to the targeted tissue, alleviating the inflammation and promoting tissue healing. This review will comprehensively collect and evaluate the targeted nanomaterials to articular cartilage in OA.